The History of UNESCO’s Lifelong Learning Policy Discourses: A Enduring Social Democratic Liberalist Project of Global Educational Development - Moosung Lee; Tom Friedrich (Adult Education Research Conference, 2008)
This article exposes precisely what ideological influences have been situated as authoritative and as marginal within UNESCO’s lifelong learning policy discourses over time, periodizing those discourses in terms of their political-economic contexts. As such, analysis reveals UNESCO’s continuous commitment to extending social democratic liberalist lifelong learning discourses of global educational development in the interest of global justice.
Keywords: UNESCO; lifelong learning; policy discourse; social democratic liberalism; historical evolution.